Effects of motivational interviewing with conventional physical therapy on rehabilitation of chronic musculoskeletal disorders: a quasi-experimental study - Ayesha Jamil; Ahsan Javed; Muhammad Awais Iqbal (Journal of the Pakistan Medical Association, 2021)
Objective: To compare effects of motivational interviewing with conventional physical therapy in rehabilitation of chronic musculoskeletal disorders versus conventional physical therapy alone. Methods: This quasi-experimental study was conducted at outpatient physical therapy clinics of Lahore from September 2017 to March 2018. Purposive sampling technique was used and participants with chronic musculoskeletal disorders were alternatively allocated to experimental group or control group. Motivational interviewing with conventional physical therapy was given in experimental group whereas control group received conventional physical therapy only. Pain intensity, functional status and exercise compliance were outcome measures. The effects of interventions were measured through visual analogue scale, patient specific functional scale and exercise compliance chart with follow-up of two weeks. Results: Results of independent sample t-test showed that pain score was significantly reduced by mean of 7.19 to 1.66 in experimental group compared to 6.83 to 2.39 in control group from 1st to 14th day (p=0.00). Functional status was significantly improved in experimental group by mean of 3.22 to 8.75 than in control group from 3.17 to 7.63 from 1st to 14th day (p=0.00). Exercise compliance was significant in experimental group with mean repetition of 12.89 and 13.93 whereas 9.48 and 10.33 in control group at 1st and 2nd week respectively (p=0.00). Within-group effects of pain intensity, functional status and exercise compliance were also significant using paired sample t-test (p=0.00). Conclusion: Integration of Motivational Interviewing with conventional physical therapy was found to decrease pain and functional limitations and improve exercise compliance. Continuous.....